Assessment of bovine tuberculosis in dairy farms and its public health importance in and around Adigrat District - Hadush, A. (Mekelle University, 2015)
A cross sectional study was conducted from September 2014 to June 2015 on 384 cattle from 68 dairy farms in and around Adigrat District, North East Ethiopia, to determine the prevalence and assessment of bovine tuberculosis (BTB) and its public health significance, camparatve intradermal tuberculin test(CIDT) and microbiological tests were used in the diagnosis of BTB in dairy animals where as questionnaire survey was conducted on 120 household members in order to observe potential risk factors responsible for the occurrence of the disease in human subjects. The CIDT was performed in 212 cross breed and 172 local breed dairy cattle. The individual animal and herd level tuberculosis prevalence were11.72% (45/384) and 36.76% (25/68) at cut-off > 4 mm, respectively. Exotic breed (OR= 3.09, 95% , CI: 1.22-7.93), intensive management system (OR= 2.64, 95% , CI: 1.01-6.92), poor body condition (OR= 3.14, 95%, CI; 1.09-9.06), large herd size (OR= 3.29, 95%, CI: 1.04-6.25) and coughing symptoms and presence of BTB(OR= 56.42, 95%, CI: 19.54-136.31) were the major risk factors significantly associated with the occurrence of tuberculosis in cattle. Of the 120 respondents only 23 (19.17%) have recognized or have heard about zoonotic importance of BTB and 19 (15.83%) were award of BTB which affect animals. The microbiological test of milk culture revealed that only13.04% (3/23) were grow on Lowenstein Jensen medium pyruvate but there were no growth on LJ medium glycerinated. Based on the finding awareness creation and test and slaughter policy should be introduced to the study district and to the region at large to decrease the public health problem and production loss.